Liang Song Kaifeng Lin'an huang cheng gong yuan yan jiu - Zhang, Jing (Qi Lu shu she, 2008)
Abstract
Keywords: Palaces / China / Kaifeng Shi; Palaces / China / Lin'an Xian; Architecture / China / History / Song-Yuan dynasties, 960-1368; Architecture / China / Kaifeng Shi; Architecture / China / Lin'an Xian; Architecture; Architecture / Song-Yuan dynasties; Palaces; Architektur; Geschichte; China; China / Kaifeng Shi; China / Lin'an Xian